Faktor-Faktor yang Mempengaruhi Non Performing Loan pada Perbankan di Indonesia - Albertha Daisy Arya Palupi; Fika Azmi (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2019)
This study aims to examine the internal and external factors that influence Non-Performing Loans in banks in Indonesia. Internal factors consist of Loan to Deposit Ratio, Operating Expenses for Operating Income, Prime Lending Rate. Meanwhile external factors consist of inflation and exchange rates. The sample in this study is Bank Umum Swasta Nasional Devisa listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling method. Data samples obtained were 84 data from 21 Bank Umum Swasta Nasional Devisa. Analysis of research data using multiple linear regression processed using the SPSS 22 program. The results showed that the variables of internal factors, namely Loan to Deposit Ratio, Operating Expenses on Operating Income and Loans Base Interest Rate affect the Non Performing Loan. While the external factor variables namely inflation and the exchange rate do not affect the Non Performing Loan.